Pertumbuhan Bibit Jeruk Asal Kuok Hasil Okulasi pada Berbagai Tingkat Naungan dan Umur Batang Bawah - Gusriani, Gusriani; Septirosya, Tiara; Darmawi, Ahmad (Universitas Perjuangan Tasikmalaya, 2019)
Citrus that comes from Kuok is one of famous local comodity in Riau Province with limited production. To improve the production of citrus it can be done by serving the superior seed throught budding. Rootstock aged and shading levels give effect to the success of budding process. The aims of the study were to obtain the best shade level, suitable rootstock aged and the interaction of rootstock aged with shade level on budding success. This study was conducted on December 2018 to March 2019 at the Experimental Field, Faculty of Agriculture and Animals Science, Islam State University of Sultan Syarif Kasim Riau. This study used split plot design with two factors, shading levels (0%, 50%, 70%) and rootstock aged (4, 8, 12 month) with three replications. The parameters this measured in this study were growth percentage of buds, percentage of sprout, percentage of dormancy, bud burst time, length of buds and number of leaves. The results showed that shade level of 0% and the age of rootstock 4 months produced the best growth of citrus seedlings. There is interaction between the shade level 0% and rootstock aged 12 month to the growth of the budding citrus seedlings.